2011
DOI: 10.1620/tjem.223.277
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Ligand 16 as a Prognostic Marker in Patients with Intermediate Coronary Artery Lesions: A 2-Year Follow-Up Study

Abstract: There is no reliable way to identify the high-risk patients with intermediate coronary artery lesions (diameter stenosis 20%-70%) in early stage. Soluble CXC chemokine ligand 16 (CXCL16) is a newly discovered chemokine that can mediate inflammatory responses. It is released by proteolytic cleavage of its membrane-bound form, named scavenger receptor for phosphatidylserine and oxidized lipoprotein (SR-PSOX) that can promote the uptake of oxidized low-density lipoprotein cholesterol by macrophages. We have hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The predictive value of CXCL16 has also been studied in stable CAD, showing an association with a composite of all-cause death, non-fatal MI, revascularization and hospitalization for angina pectoris during 24 months of follow-up. 25 CXCL16 has furthermore been found to predict the risk of MI in healthy volunteers. 26 Accordingly, CXCL16 may be a new predictor of adverse outcome across the whole spectrum of CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive value of CXCL16 has also been studied in stable CAD, showing an association with a composite of all-cause death, non-fatal MI, revascularization and hospitalization for angina pectoris during 24 months of follow-up. 25 CXCL16 has furthermore been found to predict the risk of MI in healthy volunteers. 26 Accordingly, CXCL16 may be a new predictor of adverse outcome across the whole spectrum of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Several previous studies have found higher serum levels of CXCL16 in ACS versus stable CAD and controls. 17,[21][22][23] There are, however, only a few prospective studies investigating the use of CXCL16 as a risk marker in CAD 6,[24][25][26][27] , and only one of these included patients from an ACS population 6,24 .…”
Section: Introductionmentioning
confidence: 99%
“…After 2 years of follow‐up, the upper plasma sCXCL16 quartile was also independently associated with adverse outcomes (including all‐cause death, MI, and revascularization) in these patients. 65 Based on these studies, circulating sCXCL16 may have strong promising potential as a clinical biomarker for predicting MI occurrence and for the diagnosis and prognosis of MI (Table 2 ).…”
Section: Association Between Each Sr and ...mentioning
confidence: 99%
“…Serum sCXCL16 level influenced by pro-inflammatory hs-CRP is also suggested as a peripheral diagnostic biomarker for diabetic patients with coronary artery disease (CAD) [ 20 ]. Increased serum sCXCL16 levels, as a strong independent indicator of long-term mortality [ 20 , 21 ], are prognostically unfavorable in ACS patients and patients with intermediate coronary lesions [ 21 ]. Recently, in a subgroup of 5142 patients randomized in the PLATO trial (Platelet Inhibition and Patient Outcome), serum sCXCL16 levels were shown to be independently associated with cardiovascular death and morbidity in ACS patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%